2011
DOI: 10.1103/physrevlett.107.148103
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Synchronized Beating during the Regrowth of Eukaryotic Flagella

Abstract: A fundamental issue in the biology of eukaryotic flagella is the origin of synchronized beating observed in tissues and organisms containing multiple flagella. Recent studies of the biflagellate unicellular alga Chlamydomonas reinhardtii provided the first evidence that the interflagellar coupling responsible for synchronization is of hydrodynamic origin. To investigate this mechanism in detail, we study here synchronization in Chlamydomonas as its flagella slowly regrow after mechanically induced self-scissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
72
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 35 publications
9
72
0
1
Order By: Relevance
“…Flagella have often been suggested to synchronize due to interflagellar hydrodynamic interactions. This view has been supported by several theoretical studies [3,4,12,13] and recent experiments [14,15]. Recently, another view has emerged, suggesting that the cell rocking motion causes synchronization by creating synchrony-restoring hydrodynamic drag on the flagella [16,17].…”
supporting
confidence: 50%
“…Flagella have often been suggested to synchronize due to interflagellar hydrodynamic interactions. This view has been supported by several theoretical studies [3,4,12,13] and recent experiments [14,15]. Recently, another view has emerged, suggesting that the cell rocking motion causes synchronization by creating synchrony-restoring hydrodynamic drag on the flagella [16,17].…”
supporting
confidence: 50%
“…Analysis of phase-slips allowed a previous, indirect estimate of flagellar phase fluctuations, corresponding to Q≈25 for the quality factor of individual flagella [10]. A latter study indicated a length-dependence of Q, with corresponding Q ranging from ≈70−120 for length increasing from 6µm to 12µm [33]. Interestingly, flagellar synchronization in Chlamydomonas seems to operate just below a tolerable level of noise: Consider the approximate dynamics of the phase difference δ between two identical, coupled oscillators,δ = −λ/T sin δ + ζ, where ζ is Gaussian white noise with ζ(t)ζ(t ) = 4Dδ(t−t ) [10,34].…”
mentioning
confidence: 99%
“…A similar mechanism was recently discovered in the biflagellate eukaryote Chlamydomonas reinhardtii (18). This unicellular green alga actively redirects its swimming motion through occasional desynchronization of its two cilia (19), although it is still debated whether this effect is of mechanical (20) or hydrodynamic (21,22) origin. Experiments (23) show that the alga's reorientation dynamics can lead to localization in shear flow (24,25), with potentially profound implications in marine ecology.…”
mentioning
confidence: 99%